PENGARUH POLIMER, TEKNIK PENCAMPURAN DAN DURASI PENGGILINGAN TERHADAP PROFIL DISOLUSI FENILBUTAZON - Liongbong, Albert
Phenylbutazone is an NSAID that is included in BCS class II drugs in the Biopharmaseutic Classification System, namely drugs with low solubility and high permeability. Because of the low dissolution rate, efforts were made to increase the dissolution rate by making physical mixture and solid dispersion. In this study, phenylbutazone solid dispersions are made using two carriers, poloxamer 407 and PVP K-30. The method used in making solid dispersions is the solvent evaporation method. Each carrier is made into solid dispersion and physical mixture in three different phenylbutazone concentration, 2:1, 1:1, and 2:3. In the making of physical mixtures, phenylbutazone and carrier polymers are sifted using mesh number 40 separately, then mixed using turbula mixer. Solid dispersions is made by solvent evaporation method. Phenylbutazone and the carrier polymer were dissolved in ethanol solvent, then the solvent was evaporated with a vacuum rotary vaporator and oven. For the manufacture of solid dispersions A, the mixture is evaporated slowly while for the manufacture of solid dispersions B, a high temperature difference is made between the sample solution and the cooling solution so that the crystals cannot form. To determine the effect of polymers and solvents, tests were also carried out for pure phenylbutazone and recrystallized phenylbutazone. All samples are sifted using mesh number 40, then crushed with a grinding machine for 0, 10, 20, and 30 minutes; and then sifted again with mesh number 40 for each grinding step. The milled sample is used for dissolution testing and SEM. Dissolution and efficiency measurements of each sample were obtained from UV-Vis spectrophotometer analysis at a wavelength of 264 nm. Based on the experiments conducted, DB PLX 2:3 without grinding and DB PVP 2:3 without grinding; has the best dissolution profile of 94.87 ± 0.48% and 93.26 ± 0.72% respectively. SEM characterization shows the crystals difference between physical mixtures, solid dispersion A and solid dispersion B, other than that grinding tend to form aggregates.